Participant observer. (Women's Review of Books, 2001)
Interviews computer programmer and author Ellen Ullman on the facts and fictions about computer technology. Information on her book `Close to the Machine: Technophilia and Its Discontents'; Views on writing computer codes; Impact of technology on women.